Late Systolic Myocardial Loading Is Associated With Left Atrial Dysfunction in Hypertension. (June 2017) - Chirinos, Julio A.; Phan, Timothy S.; Syed, Amer A.; Hashmath, Zeba; Oldland, Harry G.; Koppula, Maheswara R.; Tariq, Ali; Javaid, Khuzaima; Miller, Rachana; Varakantam, Swapna; Dunde, Anjaneyulu; Neetha, Vadde; et al.
Abstract : Background—: Late systolic load has been shown to cause diastolic dysfunction in animal models. Although the systolic loading sequence of the ventricular myocardium likely affects its coupling with the left atrium (LA), this issue has not been investigated in humans. We aimed to assess the relationship between the myocardial loading sequence and LA function in human hypertension. Methods and Results—: We studied 260 subjects with hypertension and 19 normotensive age- and sex-matched controls. Time-resolved central pressure and left ventricular geometry were measured with carotid tonometry and cardiac magnetic resonance imaging, respectively, for computation of time-resolved ejection-phase myocardial wall stress (MWS). The ratio of late/early ejection-phase MWS time integrals was computed as an index of late systolic myocardial load. Atrial mechanics were measured with cine-steady-state free-precession magnetic resonance imaging using feature-tracking algorithms. Compared with normotensive controls, hypertensive participants demonstrated increased late/early ejection-phase MWS and reduced LA function. Greater levels of late/early ejection-phase MWS were associated with reduced LA conduit, reservoir, and booster pump LA function. In models that included early and late ejection-phase MWS as independent correlates of LA function, late systolic MWS was associated with lower, whereas early systolic MWS was associated with greater LA function, indicating an effect of the relative loading sequence (late versus early MWS) on LA function. These relationships persisted after adjustment for multiple potential confounders. Conclusions—: A myocardial loading sequence characterized by prominent late systolic MWS was independently associated with atrial dysfunction. In the context of available experimental data, our findings support the deleterious effects of late systolic loading on ventricular–atrial coupling. Abstract : Supplemental Digital Content is available in the text.